2010
DOI: 10.1002/pssa.201000016
|View full text |Cite
|
Sign up to set email alerts
|

Heating rate effects on the TL characteristics of hot filament CVD diamond film

Abstract: The thermoluminescence (TL) glow curve of polycrystalline chemically vapor deposited (CVD) diamond is strongly dependent on the heating rate used. In the present work, we report results about the heating rate effects on a 500 mm hot filament (HF) CVD diamond film grown on silicon substrate using a precursor gas mixture composition of CH 4 (5 sccm)-CO(10 sccm)-H 2 (400 sccm). The irradiations were performed with 60 Co source. The TL measurements were carried out at different heating rates in the 2-30 K/s range.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The increase of the peak maximum should be accompanied by the narrowing of the peak in such manner that the total peak area remains constant 1. There are a number of TL phosphors (and CVD diamond among of them 2–5), for which the peak area decreases with the increase of the heating rate β . Gorbics et al 6, 7 were the first who studied TL in six dosimetry phosphors by varying the heating rate and found that the measured TL decreased for higher heating rates.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of the peak maximum should be accompanied by the narrowing of the peak in such manner that the total peak area remains constant 1. There are a number of TL phosphors (and CVD diamond among of them 2–5), for which the peak area decreases with the increase of the heating rate β . Gorbics et al 6, 7 were the first who studied TL in six dosimetry phosphors by varying the heating rate and found that the measured TL decreased for higher heating rates.…”
Section: Introductionmentioning
confidence: 99%